A "Passport to Freedom"? COVID-19 and the Re-bordering of the World. (June 2021) - TAZZIOLI, Martina
Abstract : This paper argues that COVID-19 has triggered a multiplication of heterogeneous bordering mechanisms that, far from stopping movement as such, have enhanced hierarchies of mobility. In particular, it shows that a confinement continuum has been put in place in the name of the "contain to protect" principle: migrants have been subjected to protracted lockdown measures in the name of their own protection. The piece concludes by interrogating how to rearticulate critique in COVID times in light of the enforcement of discriminatory "passports to freedom" (COVID-19 travel certificates).